2019
DOI: 10.1002/14651858.cd012484.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blockers for suspected or diagnosed acute myocardial infarction

Abstract: BackgroundCardiovascular disease is the number one cause of death globally. According to the World Health Organization, 7.4 million people died from ischaemic heart diseases in 2012, constituting 15% of all deaths. Acute myocardial infarction is caused by blockage of the blood supplied to the heart muscle. Beta-blockers are o en used in patients with acute myocardial infarction. Previous meta-analyses on the topic have shown conflicting results ranging from harms, neutral e ects, to benefits. No previous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 210 publications
1
23
0
3
Order By: Relevance
“…carried out a systematic review on the effect of beta-blockers on the outcomes of patients with myocardial infarction. [ 5 ] In this review, the Population was patients with suspected or confirmed myocardial infarction, the Intervention was beta-blocker therapy, the Comparator was either placebo or no intervention, and the Outcomes were all-cause mortality and major adverse cardiovascular events. The review question was “ In patients with suspected or confirmed myocardial infarction, does the use of beta-blockers affect mortality or major adverse cardiovascular outcomes?…”
Section: The Process Of a Systematic Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…carried out a systematic review on the effect of beta-blockers on the outcomes of patients with myocardial infarction. [ 5 ] In this review, the Population was patients with suspected or confirmed myocardial infarction, the Intervention was beta-blocker therapy, the Comparator was either placebo or no intervention, and the Outcomes were all-cause mortality and major adverse cardiovascular events. The review question was “ In patients with suspected or confirmed myocardial infarction, does the use of beta-blockers affect mortality or major adverse cardiovascular outcomes?…”
Section: The Process Of a Systematic Reviewmentioning
confidence: 99%
“…included all randomized clinical trials, irrespective of setting, blinding, publication status, publication year, or language, and reported outcomes, that had used any beta-blocker and in a broad range of doses. [ 5 ]…”
Section: The Process Of a Systematic Reviewmentioning
confidence: 99%
See 3 more Smart Citations